2021
DOI: 10.1007/s00384-021-03985-9
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death ligand 1 (PD-L1) in colon cancer and its interaction with budding and tumor-infiltrating lymphocytes (TILs) as tumor-host antagonists

Abstract: Purpose To analyze the role of programmed death ligand 1 (PD-L1) immunohistochemisty in the context of tumor microenvironment in colon cancer (CC) with focus on the interaction between tumor budding and tumor-infiltrating lymphocytes (TILs) and to elucidate its potential value for immunooncologic treatment decisions. Methods Three hundred forty seven patients with CC, stages I to IV, were enrolled. PD-L1 immunohistochemistry was performed using two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
(70 reference statements)
4
13
0
Order By: Relevance
“…Our findings are in line with mounting evidence supporting a relationship between PD‐L1 expression in immune cells and more favourable clinical outcomes 17,18 …”
Section: Discussionsupporting
confidence: 90%
“…Our findings are in line with mounting evidence supporting a relationship between PD‐L1 expression in immune cells and more favourable clinical outcomes 17,18 …”
Section: Discussionsupporting
confidence: 90%
“…The second overlapping protein between the two indices, PDCD1, also known as programmed cell-death protein 1 (PD-1), has been widely studied, and the axis of PD-1 and its ligand, PD-L1, are considered the most successful target for immune checkpointblockade therapy to date [31]. PD-L1 has been shown to be a prognostic marker in several cancer types [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the tumor microenvironment, a low tumor budding /high TILs status could be a potential candidate for anti-PD-L1 treatment. While the relationship between tumor budding and PD-L1 expression is still not clear, Lang-Schwarz et al (4) reported an inverse relationship between tumor budding and PD-L1 expression in colorectal cancer. Furthermore, they found that a low tumor budding/high TILs status showed higher PD-L1 expression levels than other combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor stroma percentage (TSP) and immune response factors, such as tumor-infiltrating DOI:10.34172/ipp.2022.31365 lymphocytes (TILs), are identified as signs of tumor progression. The interactions among these factors contributed to the development of immunotherapy through the identification of multiple immune checkpoints (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation